A Long‐Lived Planetesimal Dynamo Powered by Core Crystallization. Issue 6 (16th March 2021) - Maurel, Clara; Bryson, James F. J.; Shah, Jay; Chopdekar, Rajesh V.; T. Elkins‐Tanton, Linda; A. Raymond, Carol; Weiss, Benjamin P.
Abstract: The existence of numerous iron meteorite groups indicates that some planetesimals underwent melting that led to metal‐silicate segregation, sometimes producing metallic cores. Meteorite paleomagnetic records suggest that crystallization of these cores generated dynamo magnetic fields. Here we describe the magnetic history of the partially differentiated IIE iron meteorite parent body. This is the first planetesimal for which we have a time‐resolved paleomagnetic record constrained by 40 Ar/ 39 Ar chronometry spanning several tens of million years (Ma). We find that the core of the IIE parent body generated a dynamo, likely powered by core crystallization, starting before 78 ± 13 Ma after solar system formation and lasting at least 80 Ma. Such extended core crystallization suggests that the core composed a substantial fraction of the body ( ≳ 13%–19% core‐to‐body radius ratio depending on the body's radius), indicating efficient core formation within some partially differentiated planetesimals. Plain Language Summary: Planetesimals were the first planetary bodies that formed in the solar system and meteorites are fragments of these planetesimals. Within the first million years of the solar system, some planetesimals melted and formed metallic cores overlain by a rocky mantles. The loss of heat and release of buoyant fluids generated through the crystallization of these cores could have caused the residual liquid to churn, generating currents that created a magnetic field by the dynamo effect. Some meteorites contain minerals that align their magnetic moments with such magnetic fields, analogous to a compass needle in Earth's field. Even though the ancient field disappeared billions of years ago, this alignment can still be retained by meteorites today. Because core solidification and generation of magnetic fields are intrinsically related, the magnetic record of meteorites is a powerful proxy for investigating the solidification and thermal history of planetesimals. Here, we present a time‐resolved record captured by three meteorites from the same parent planetesimal of a magnetic field powered by the solidification of their parent planetesimal's core. It is the most extended record of such fields for which we have absolute ages and supports the hypothesis that some planetesimals efficiently melted and formed significantly large metallic cores. Key Points: Using IIE iron meteorites, we present the most extended record of dynamo activity on a planetesimal constrained by radiometric dating This extends the epoch of planetesimal dynamo activity to 160 Ma after solar system formation, indicating protracted core crystallization This argues for efficient metal‐silicate separation to form a central metallic core with a radius representing >13%–19% of the body radius